2020
DOI: 10.1109/access.2020.2986608
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Reality for Learning of Children and Adolescents With Autism Spectrum Disorder (ASD): A Systematic Review

Abstract: This paper presents a systematic review of relevant primary studies on the use of augmented reality (AR) to improve various skills of children and adolescents diagnosed with autism spectrum disorder (ASD) from years 2005 to 2018 inclusive in eight bibliographic databases. This systematic review attempts to address eleven specific research questions related to the learing skills, participants, AR technology, research design, data collection methods, settings, evaluation parameters, intervention outcomes, genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(75 citation statements)
references
References 87 publications
2
62
0
4
Order By: Relevance
“…Despite the promising results of the application of AR in interventions in children and adolescents with ASD, at present time, only two previous reviews [ 15 , 16 ] about ASD and AR have been carried out. A recent review focused on the use of AR for intervention in people with ASD [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the promising results of the application of AR in interventions in children and adolescents with ASD, at present time, only two previous reviews [ 15 , 16 ] about ASD and AR have been carried out. A recent review focused on the use of AR for intervention in people with ASD [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Only 16 studies were identified, and many of them were presentations to congresses. Likewise, the review by Khowaja et al [ 16 ] provided the state-of-the-art research regarding studies utilizing AR for children and adolescents with ASD to learn different skills. These recent reviews on the application of augmented reality (AR) technologies in ASD highlight the need for a better evidence base for the utility of AR in treatment and rehabilitation of individuals with special needs.…”
Section: Introductionmentioning
confidence: 99%
“…Los 26 estudios seleccionados se han agrupado en función de los contextos de intervención en donde se han llevado a cabo: a) Educativo Los estudios ligados al ámbito educativo abordan la efectividad de determinados recursos didácticos apoyados en RA y adaptados a las necesidades del alumnado con TEA (Arief & Efendi, 2018;Chen et al, 2016;Kolomoiets & Kassim, 2018;Sahin et al, 2018a;Taryadi & Kurniawan, 2018). Otros indagan en la utilidad de la RA para facilitar el reconocimiento emocional y las habilidades sociales (Kellems et al, 2020), su autonomía (McMahon et al, 2012) e interacción social (Khowaja et al, 2020;Lee et al, 2018a).…”
Section: Muestraunclassified
“…Junto al de Keshav et al (2017) que analiza la usabilidad que ofrecen sistemas como Brain Power Autism System (BPAS) para personas con TEA. Finalmente, se incluyen la revisión sistemática de Khowaja et al (2020) centrada en analizar la potencialidad de la RA para desarrollar distintas competencias en el alumnado con TEA; y la de Adnan et al (2018) que reseña diferentes intervenciones con RA en personas de este colectivo.…”
Section: Muestraunclassified
See 1 more Smart Citation